Hubungan Pola Asuh Ibu Dalam Pemberian Makanan Dengan Kejadian Stunting Pada Balita - Wa Ode Hasriati (Madu Jurnal Ilmu Kebidanan, 2026)
Stunting remains one of the major nutritional problems among toddlers and is a condition of growth failure caused by chronic malnutrition over a long period, resulting in children having shorter height than the standard for their age. Maternal parenting patterns, especially in feeding practices, are considered one of the important factors influencing the incidence of stunting. This study aimed to analyze the relationship between maternal parenting patterns in feeding and the incidence of stunting among toddlers. This research used a correlational design with a cross-sectional approach. The population consisted of all mothers of toddlers and toddlers in the working area of Bataraguru Health Center until July 2024, totaling 605 respondents. A sample of 60 respondents was selected using convenience sampling technique. Data were collected using questionnaires and toddler height measurements, then analyzed using the Rank-Spearman test with a significance level of ρ < 0.05. The results showed that most respondents applied democratic parenting patterns in feeding, with 43 respondents (71.7%). Around 30 toddlers (50%) had normal height status. Statistical analysis showed no significant relationship between maternal parenting patterns in feeding and the incidence of stunting among toddlers (ρ = 0.691). It can be concluded that there is no significant relationship between maternal feeding parenting patterns and stunting incidence, although appropriate parenting tends to support better toddler growth outcomes.